Smoking and non-communicable disease mortality: prospective study of the population of 40-59-year-old men - R. Sh. Mamutov; D. A. Mamaradzhapova; A. A. Aminov; O. U. Urinov (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the prognostic role of cigarette smoking in the end-point development during the 25-year prospective follow-up of 40-59-year-old men. Material and methods. The baseline examination of a representative sample of Tashkent City men took place in 1979-80. During the 25-year follow-up (up to 2005), the death certificate data were collected for the deceased participants of the initial study — men aged 40-59 years at baseline. All-cause mortality, cardiovascular disease (CVD) mortality, cancer mortality, and their association with smoking were analyzed. Results. Out of 862 participants who smoked at baseline, 56,7 % died during 25 years of the prospective follow-up. Among smokers, 25-year all-cause mortality was 34,4 per 1000 person-years, while CVD and cancer mortality was 18,7 and 7,0 per 1000 person-years, respectively. Smoking was a strong predictor of 25-year all-cause mortality: compared to never-smokers, all-cause, CVD, and cancer mortality in smokers was 1,8, 1,6, and 3,5-4,6 times higher. Conclusion. Among all deceased participants, the prevalence of baseline smoking was 61,2 %, while among people who died from CVD or cancer, it was 58,9 % and 71 %, respectively. Among men who were regular smokers at baseline, the levels of all-cause, CVD, and cancer mortality were 1,5, 1,6, and 3,3 times higher than among neversmokers. There was a direct linear association between the contribution of smoking in the end-point development and the follow-up length.